2012
DOI: 10.3390/app2020303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Superparamagnetic Nanoparticle Clusters on the Polymerase Chain Reaction

Abstract: Abstract:The polymerase chain reaction (PCR) method is widely used for the reproduction and amplification of specific DNA segments, and a novel PCR method using nanomaterials such as gold nanoparticles has recently been reported. This paper reports on the effects of superparamagnetic nanoparticles on PCR amplification without an external magnetic field, and clarifies the mechanism behind the effects of superparamagnetic particle clusters on PCR efficiency by estimating the structures of such clusters in PCR. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In the sample with only the preconcentration step, the Ab-MNPs can improve the detection by providing higher numbers of bacterial cells to the PCR and qPCR. However, Ab-MNPs and cell debris can inhibit DNA polymerase, so that the benefit offered by the bacterial preconcentration is decreased due to the modest interference from Ab-MNPs and cell debris in DNA amplification [ 22 ]. By including both preconcentration and purification steps in the 3DpmFD, only purified gDNA can be provided to the PCR and qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…In the sample with only the preconcentration step, the Ab-MNPs can improve the detection by providing higher numbers of bacterial cells to the PCR and qPCR. However, Ab-MNPs and cell debris can inhibit DNA polymerase, so that the benefit offered by the bacterial preconcentration is decreased due to the modest interference from Ab-MNPs and cell debris in DNA amplification [ 22 ]. By including both preconcentration and purification steps in the 3DpmFD, only purified gDNA can be provided to the PCR and qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…Quantification of these results confirmed that the device completely removed all residual SPIONs from the diamagnetically separated blood plasma, and this capability would enable various bioanalytical applications, including PCR, which are often interfered with iron oxide nanoparticles. [44]…”
Section: Figure 2 Experimental Validation Of Theoretical Prediction For Diamagnetic Repulsion Of Blood Cells A)mentioning
confidence: 99%
“…Their results indicated that temperature profile becomes more flat near the middle of two disks with the increase of injection but the opposite trend is observed with increase of expansion ratio. Some relevant studies on the topic can be seen from the list of references [14][15][16][17][18][19][20][21][22].…”
Section: Open Accessmentioning
confidence: 99%